Additional logarithmic utility of an insider - Jürgen Amendinger; Peter Imkeller; Martin Schweizer (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
In this paper, we consider a security market in which two investors on different information levels maximize their expected logarithmic utility from terminal wealth. While the ordinary investor's portfolio decisions are based on a public information flow, the insider possesses from the beginning extra information about the outcome of some random variable G, e.g., the future price of a stock. We solve the two optimization problems explicitly and rewrite the insider's additional expected logarithmic utility in terms of a relative entropy. This allows us to provide simple conditions on G for the finiteness of this additional utility and to show that it is basically given by the entropy of G.
urn:nbn:de:kobv:11-10056711
Keywords: 330; insider trading; entropy; utility maximization; initial enlargement of filtrations; relative entropy